Writing Equipment - Willi, Anna (Manual of Roman Everyday Writing, 2021)
Manual of Roman Everyday Writing Volume 2: Writing Equipment is a detailed study of Roman writing equipment, offering a comprehensive, lavishly illustrated and much-needed survey of the material resources for the production of everyday written documents in the Roman empire. Sections on the social aspects of writing, on writing techniques, and on the evidence that we can use to research such topics are followed by a comprehensive catalogue. Drawing on archaeological, literary, and iconographic evidence, it describes the surfaces of materials commonly used to take writing, instruments made for writing by incision and scratching or with ink pens, and relevant accessories such as inkwells and writing cases. In each case, important finds as well as research publications are included to assist more detailed study. The catalogue is supplemented by a collection of literary passages in Latin and translation, including the detailed description by Pliny the Elder of the process of making papyrus (Natural History 13.74-82), and by a glossary of the relevant terminology in seven languages.